An overview of microneedle applications, materials, and fabrication methods - Faraji Rad, Zahra; Prewett, Philip D; Davies, Graham J (Beilstein journal of nanotechnology, 2021)
Microneedle-based microdevices promise to expand the scope for delivery of vaccines and therapeutic agents through the skin and withdrawing biofluids for point-of-care diagnostics – so-called theranostics. Unskilled and painless applications of microneedle patches for blood collection or drug delivery are two of the advantages of microneedle arrays over hypodermic needles. Developing the necessary microneedle fabrication processes has the potential to dramatically impact the health care delivery system by changing the landscape of fluid sampling and subcutaneous drug delivery. Microneedle designs which range from sub-micron to millimetre feature sizes are fabricated using the tools of the microelectronics industry from metals, silicon, and polymers. Various types of subtractive and additive manufacturing processes have been used to manufacture microneedles, but the development of microneedle-based systems using conventional subtractive methods has been constrained by the limitations and high cost of microfabrication technology. Additive manufacturing processes such as 3D printing and two-photon polymerization fabrication are promising transformative technologies developed in recent years. The present article provides an overview of microneedle systems applications, designs, material selection, and manufacturing methods.